Analysis of Rice Field Rat (Rattus argentiventer) Attacks After Owl (Tyto alba) Application in Karawang Regency, West Java - Reza Rama Gunada; Swastiko Priyambodo; Dadan Hindayana (The University of Lampung, 2025)
Environmentally friendly control using biological methods for rice field rats is currently being carried out, one of which is using the natural enemy of rice field rats, namely the owl predator which can control rice field rat pests without damaging rice and land or causing pollution. This research aims to evaluate the value of losses experienced by farmers caused by rice field rat pests in Karawang Regency, analyze farmers' perceptions and behavior towards controlling rice field rat pests using owls, implementation of rice field rat pest control in Karawang Regency, and policy priorities that can be implemented and taken to optimize the sustainable use of owls in the context of controlling rice field rat pests in Karawang Regency. The method used is a survey and field observation which includes observing the number of active rat nests, calculating the percentage of attacks, calculating the number of owls after introduction, calculating crop production, and farmers' perceptions of controlling field rats using owls, as well as data analysis. Results showed that the use of owls is effective in controlling rice field rat pests, this is shown by the correlation between the high number of owls and the reduced level of rat attacks in rice field areas. Keywords: Ricefield rat, Owl, Policy, Predator, Rice.